Analisis Produksi Aci Sagu di Desa Ulupohara Kecamatan Besulutu Kabupaten Konawe - O, Oktifiani; S, Surni; Taridala, Sitti Aida Adha (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This study aims to determine the sago starch production process in Ulupohara Village, Besulutu District, Konawe Regency. This study was conducted from July to August 2022 in Konawe Regency with a sample of 10 people or 2 groups of respondents. The data analysis used in this study is quantitative descriptive analysis. Quantitative descriptive analysis is used to determine the sago starch production process. namely land, labor, capital and experience in processing sago. These four factors have a significant effect on the level of sago starch production.